Pengaruh Model Kooperatife Tipe Think Pair and Share Terhadap Hasil Belajar IPA oleh Siswa Kelas IV MIS Aisyiyah Wilayah Sumut Tahun Ajaran 2023/2024 - Abliani, Poppy; Ramadhani, Mastari; Malinda, Leni (Medan Resource Center, 2024)
This study aimed to address the low learning outcomes in science education for fourth-grade students at MIS Aisyiyah Elementary School, North Sumatra, where teaching tends to be teacher-centered. To remedy this issue, the Think Pair and Share cooperative learning model was implemented. An experimental research method was employed, involving 53 students divided into two groups. The experimental group used the Think Pair and Share model, while the control group applied conventional teaching methods. Data were collected through both test-based measures (pretest and posttest) and non-test observations, including teacher performance and student activity during the learning process. The results revealed a significant improvement in the experimental group, with an average score of 84.40, compared to 69.46 in the control group. It can be concluded that the implementation of the Think Pair and Share cooperative learning model positively impacts science learning outcomes for fourth-grade students. It is recommended that teachers adopt this model to enhance the effectiveness of science education in similar contexts.